2019
DOI: 10.3354/meps12881
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of oil into diatom aggregates

Abstract: Rolling table experiments were conducted to investigate the incorporation of 2 types of dispersed oil into diatom aggregates. The goal was to provide specific input parameters for aggregation models that predict the transport of oil to depth via marine snow-sized aggregates (> 0.5 mm). The amount of oil incorporated into aggregates is a function of both aggregated biomass and dispersed oil concentration. The maximum carrying capacity of diatom aggregates for dispersed oil likely lies at ~40% of the aggregated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 99 publications
4
35
0
Order By: Relevance
“…pseudonana between Controls, WAF and DCEWAF ( Fig 1 ). For the latter, similar observations have been reported previously [ 58 , 63 ]. A negative effect from the addition of Corexit on aggregate formation was also observed in a mesocosm study with nearshore surface water [ 11 , 62 ], other roller table studies [ 58 ] and bottle experiments [ 64 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…pseudonana between Controls, WAF and DCEWAF ( Fig 1 ). For the latter, similar observations have been reported previously [ 58 , 63 ]. A negative effect from the addition of Corexit on aggregate formation was also observed in a mesocosm study with nearshore surface water [ 11 , 62 ], other roller table studies [ 58 ] and bottle experiments [ 64 ].…”
Section: Discussionsupporting
confidence: 91%
“…These observations were similar if not identical to those found by Bacosa et al [ 73 ]. Passow et al [ 63 ] also showed that aggregates vary in their carrying capacity for oil compounds compared to the surrounding seawater. In agreement with this observation, we found that the PAH composition of AGG and SSW were significantly different, with PAHs such as Phenanthrenes, Anthracenes, Chrysenes, Fluorenes, Fluoranthenes, Pyrenes, Dibenzothiophenes and 1-Methylphenanthrene showing major variations.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the addition of ballasting mineral particles to marine particle populations frequently leads to smaller more densely packed aggregates that sink slower because of their smaller size (Hamm, 2002;Passow et al, 2014). Mucous-rich particles have been shown to float despite relatively large sizes (Azetsu-Scott and Passow, 2004;Bochdansky et al, 2016), whereas oil-or plastic-containing aggregates have been shown to sink rapidly despite the presence of substances with an excess density smaller than seawater (Long et al, 2015;Passow et al, 2019). In natural environments, particles are formed through different mechanisms, by different organisms, and under varying environmental conditions that affect aggregation (e.g., salinity, pH, minerals), ballasting (e.g., dust deposition, sediment load; Iversen and Robert, 2015;van der Jagt et al, 2018) and sinking behavior (e.g., viscosity; Taucher et al, 2014).…”
Section: Sinking Velocitymentioning
confidence: 99%
“…One fourth of all aggregates were collected for RNA analysis (2 min spin down at 12,000 rpm and discarding the supernatant, freezing in liquid nitrogen and storage at -80°C). For all other measured factors, harvest included separate sampling of the aggregate fraction (aggregates >0.5mm, Agg) and the surrounding sea water fraction (aggregates <0.5 mm and un-aggregated cells, SSW) [24]. Aggregates for sinking velocity (three aggregates per size class for 11.5 cm in a 100-mL glass graduated glassware cylinder) was collected in artificial seawater at the same temperature as experiments were conducted.…”
Section: Measurements Of Cell Density and Aggregationmentioning
confidence: 99%